2019
DOI: 10.1152/jn.00072.2019
|View full text |Cite
|
Sign up to set email alerts
|

Eye-head-hand coordination during visually guided reaches in head-unrestrained macaques

Abstract: Nonhuman primates have been used extensively to study eye-head coordination and eye-hand coordination, but the combination—eye-head-hand coordination—has not been studied. Our goal was to determine whether reaching influences eye-head coordination (and vice versa) in rhesus macaques. Eye, head, and hand motion were recorded in two animals with search coil and touch screen technology, respectively. Animals were seated in a customized “chair” that allowed unencumbered head motion and reaching in depth. In the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 128 publications
(216 reference statements)
1
19
0
Order By: Relevance
“…For example, the current review only touches on egocentric models; we have already started applying these methods to investigate the neural coding of allocentric landmarks in the gaze system (Bharmauria, Sajad, Li, et al, 2020a; Bharmauria, Sajad, Yan, Sajad, Yan, Wang, & Crawford, 2020b). We have also started using this method to differentiate gaze, head, and reach transformations in frontal cortex during coordinated eye‐head‐hand reaches (Arora et al., 2019; Nacher et al, 2019). There is no reason to not take this further afield, such as the analysis of activity in areas involved in spatial navigation and spatial memory, including the hippocampus and entorhinal cortex, against ego‐ and allocentric models during complex tasks such as natural viewing and free‐moving navigation (Gulli et al., 2020; Meister & Buffalo, 2018).…”
Section: Theoretical Implications: a New Conceptual Model For Gaze Comentioning
confidence: 99%
“…For example, the current review only touches on egocentric models; we have already started applying these methods to investigate the neural coding of allocentric landmarks in the gaze system (Bharmauria, Sajad, Li, et al, 2020a; Bharmauria, Sajad, Yan, Sajad, Yan, Wang, & Crawford, 2020b). We have also started using this method to differentiate gaze, head, and reach transformations in frontal cortex during coordinated eye‐head‐hand reaches (Arora et al., 2019; Nacher et al, 2019). There is no reason to not take this further afield, such as the analysis of activity in areas involved in spatial navigation and spatial memory, including the hippocampus and entorhinal cortex, against ego‐ and allocentric models during complex tasks such as natural viewing and free‐moving navigation (Gulli et al., 2020; Meister & Buffalo, 2018).…”
Section: Theoretical Implications: a New Conceptual Model For Gaze Comentioning
confidence: 99%
“…3, C and D) and this could account for the vertical head movement that occurred after the gaze shift ended, simultaneously with the hand movement. Adding further support to this interpreta-tion of Arora et al (2019) findings, very recent evidence by Berger et al (2020) has shown that in freely moving monkeys performing either reaches, or walk-to-reach movement sequences, the activity in frontal and parietal cortex was correlated not only with hand kinematics, but also with translational head movements. The experiments by Berger et al (2020) highlight the fact that the classic approach of constraining movement in a single or in a couple of joints that has been widely used in neurophysiological studies of motor control to facilitate data analysis and results interpretation should be revised and novel task paradigms using reaching movements under whole body motion in various behavioral constrains should be used.…”
mentioning
confidence: 63%
“…Altogether, the results of Arora et al (2019) suggest a stronger coupling of head and arm with respect to the eye that seems rather unexpected. However, a significant number of older-but also some recent-human studies are in line with their findings.…”
mentioning
confidence: 89%
See 2 more Smart Citations